Stage-Specific Effects of Silver Nanoparticles on Physiology During the Early Growth Stages of Rice - Ruxue Pan; Zailin Zhang; Ya Li; Sihong Zhu; Sumera Anwar; Jiaquan Huang; Chuanling Zhang; Liyan Yin (Plants)
Silver nanoparticles (AgNPs), widely utilized nanomaterials, can negatively affect crop growth and development. However, it remains unclear whether crops exhibit similar responses to AgNPs stress at seed germination and seedling stages. In this study, rice seeds and seedlings were exposed to AgNPs, and their growth, photosynthetic efficiency, and antioxidant systems were recorded. demonstrated significant AgNPs accumulation in rice tissues, with notable higher accumulation in seedlings exposed to AgNPs after germination compared to AgNPs exposure during germination. The roots exhibited greater AgNPs accumulation than shoots across both stages. Exposure to AgNPs during the seed germination stage, even at concentrations up to 2 mg/L, did not significantly affect growth, physiological indices, or oxidative stress. In contrast, seedlings exposed to 1 and 2 mg/L AgNPs showed significant reductions in shoot length, biomass, nutrient content, and photosynthetic efficiency. At low AgNPs concentrations, the maximum relative electron transport rate (rETRmax) was significantly reduced, while the higher concentrations caused pronounced declines in the chlorophyll a fluorescence transient curves (OJIP) compared to the control group. Antioxidant enzyme activities increased in both leaves and roots in a dose-dependent manner, with roots exhibiting significantly higher activity, suggesting that roots are the primary site of AgNPs stress responses. In conclusion, rice responds differently to AgNPs exposure at distinct developmental stages, with the seedling stage being more susceptible to AgNPs-induced stress than the seed germination stage. These findings underscore the importance of considering growth stages when assessing the food safety and environmental risks associated with AgNPs exposure.